2022
DOI: 10.1002/bio.4412
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural tuning and band gap engineering of calcium hydroxides: a novel approach by pH variation

Abstract: Here we report a simple, inexpensive, energy benign, yet novel pH‐driven chemical precipitation technique to achieve microstructural and band gap engineering of calcium hydroxide nanoparticles (CHNPs). The chemical precipitation route involved the use of 0.4–1.6 M Ca(NO3)2.4H2O solutions as the precursor and 1 M NaOH solution as the precipitator. The simple variation in precursor molarity induces a pH change from about 12.4 to 11.3 in the reactant solution. The CHNPs characterized by X‐ray diffraction (XRD), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…They reported that the synthesized CDs had a linear range 0.00080-0.0050 mg/ml and an LOD of 0.00030 mg/ml. Akash et al [47]…”
Section: Overview Of Published Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the synthesized CDs had a linear range 0.00080-0.0050 mg/ml and an LOD of 0.00030 mg/ml. Akash et al [47]…”
Section: Overview Of Published Researchmentioning
confidence: 99%
“…They reported that the synthesized CDs had a linear range 0.00080–0.0050 mg/ml and an LOD of 0.00030 mg/ml. Akash et al [47] synthesized Ca(OH) 2 via a chemical precipitation method and size modification of nanocrystallites from 5.38 to 5.26 eV just by monitoring the pH. Moreover, the rise in the nanocrystallite size decreased the bandgap energy from 5.38 to 5.26 eV for the calcium hydroxide NPs (CHNPs).…”
Section: Overview Of Published Researchmentioning
confidence: 99%